« La parole est mon domaine sur le monde » : circulation et réception de l’œuvre de Clarice Lispector au Portugal - Natália de Santanna Guerellus (Les Cahiers de Framespa)
This article has a twofold ambition: propose a panorama of the bibliography devoted to the circulation and reception of the Brazilian writer Clarice Lispector (1920-1977) on an international scale; study these two aspects in Portugal, where the question of translation is not the same as in other countries. In this sense, the analysis is based on two different categories of documents in addition to the specialized bibliography: first, I look at publications of Clarice Lispector's work in Portugal in order to identify its channels of circulation; secondly, I turn to the reception of Lispector’s works in Portugal, paying special attention to mediators. The paper thus aims at being an original contribution to the transatlantic history of writings based on the example of Brazil, as seen from another Portuguese-speaking country.